The effect of brewing time herbal tea from mother-in-law’s tongue leaves (Sansevieria trifasciata Prain) on total phenol, total flavonoid, and antioxidant activity - MAYA PRATIWI HUTABARAT; ZULKIFLI LUBIS; JANSEN SILALAHI (Universitas Syiah Kuala, 2023)
Indonesia is a tropical country known for its biodiversity, one of which is the mother-in-law’s tongue (Sansevieria trifasciata Prain). Mother-in-law’s tongue leaves extract contains bioactive compounds, such as triterpenoids, steroids, and flavonoids and tradionally used especially as antidiabetics. The phenolic and flavonoid compounds in mother-in-law’s tongue are potential antioxidants, and usually processed into herbal tea. This research aimed to determine the effect of duration brewing time herbal tea from mother-in-law’s tongue leaves (Sansevieria trifasciata Prain) on total phenol, total flavonoid, and antioxidant activity. This study using Completely Randomized Designed (CRD) with 5 treatments (different brewing time that were 1, 3, 6, 9, 12 minutes) and 3 replications. The result showed that brewing time had a significant effect on total phenol, total flavonoid, and antioxidant activity. The optimum of brewing time herbal tea from mother-in-law’s tongue leaves is 6 minutes.